THU0344 A rheumatology led pathway for the initial management of GCA improves diagnostic outcomes compared to the generalist. (15th June 2017) - Farah, Z; Gulati, M; Matheou, M; Alam, H; Hamdulay, S
Abstract : Background: Giant Cell Arteritis (GCA) is a medical emergency requiring prompt and appropriate management to prevent complications. The British Society of Rheumatology (BSR) has set out guidelines on the appropriate management of suspected GCA targeting both primary and secondary-care physicians. Hospitals increasingly use care-pathways to facilitate appropriate initial management of GCA by non-rheumatologists. Evidence is limited, however, on the impact of such interventions on patient care. Objectives: To evaluate the impact of designing a GCA care-pathway for non-rheumatologists (acute and general physicians) on patient care in terms of: (i) duration from referral to temporal artery biopsy (TAB) and rheumatology review; (ii) glucocorticoid therapy burden; and (iii) proportion of referrals with a final diagnosis of GCA Methods: We performed a retrospective study of all patients diagnosed with GCA between 3 periods: prior to introducing a GCA pathway (2007–2009), rheumatology led GCA pathway (2010–2012), and non-rheumatology led GCA pathway (2012–2016). We identified patients from a TAB database and collected general demographic data, initiation of glucocorticoid therapy, referral for TAB and rheumatology clinic, date of TAB and clinic review, biopsy findings, and final diagnosis. Results: Table 1 summarises the main findings. After introducing the rheumatology-led pathway (2010–2012), rate of referrals for TAB per month declined to 0.78, the proportion of patients having a TAB within 14 days of referral reached 100%, and the proportion of patients with a positive biopsy increased to 30% suggesting appropriate use of the pathway and an improvement in care. However introducing a non-rheumatology led GCA pathway (2012–2016), led to increased referral numbers. The proportion of TAB within 14 days decreased, and the proportion with a positive biopsy declined (17%). The non-rheumatology led GCA pathway was associated with higher glucocorticoid burden. In this cohort, 23/55 (41.8%) patients who were found not to have GCA received more than 21 days of high dose steroids (40–60mg Prednisolone) whilst awaiting rheumatology review. 4 patients whose final diagnosis was not GCA received high dose steroids for more than 30 days (max 109 days). Conclusions: Availability of a rheumatology-led GCA pathway leads to improved care for patients with suspected GCA Easy access for referral of patients with headache as assessed by the non-specialist can lead to over-use of the pathway and inappropriate referrals Non-rheumatology-led GCA pathway can lead to a high glucocorticoid burden, especially in an elderly demographic with other comorbidities Disclosure of Interest: None declared